2020
DOI: 10.1177/0148558x20953059
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Importance of Auditor Characteristics Versus Client Factors in Explaining Audit Quality

Abstract: The U.K. listed firms are used to investigate whether auditor attributes (fixed effects for audit firms, audit offices, and audit partners) add incrementally to baseline models with client controls in explaining audit quality. We document that accounting firm fixed effects add significantly to baseline models. To the extent an accounting firm can standardize its audits, there should be no differences across engagements. However, we find significant interoffice differences, and also significant inter-partner di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 76 publications
1
36
0
2
Order By: Relevance
“…The F-statistic for joint significance is large and significant, suggesting that idiosyncratic audit partner style affects BHCs' provisioning. This result is consistent with prior research, such as Gul et al (2013) and Cameran et al (2020), who study…”
Section: Evidence From the F-test Using Actual Audit Partner Assignmentssupporting
confidence: 93%
See 1 more Smart Citation
“…The F-statistic for joint significance is large and significant, suggesting that idiosyncratic audit partner style affects BHCs' provisioning. This result is consistent with prior research, such as Gul et al (2013) and Cameran et al (2020), who study…”
Section: Evidence From the F-test Using Actual Audit Partner Assignmentssupporting
confidence: 93%
“…Using data on Chinese firms, Gul et al (2013) document an increase in adjusted R 2 after adding audit partner fixed effects and conclude that audit partner characteristics affect accounting quality. Cameran et al (2020) use the same fixed effects methodology to test for partner heterogeneities in the U.K. and find that partner fixed effects have greater explanatory in explaining the variation in earnings quality, GC reporting, and audit pricing. Taylor (2011) uses Australian data for 2005 to test whether audit fees are affected by partner characteristics and finds that audit fees are significantly affected by partners' innate characteristics.…”
Section: Prior Literaturementioning
confidence: 99%
“…Bol et al (2018) indicated that tacit knowledge sharing is essential in developing individual auditors and building audit firms' human capital, leading to higher quality audits. Likewise, Cameran et al (2020) concluded that tacit knowledge sharing is positively associated with the firm's internal evaluation of auditors' competencies and audit quality. According to the argument above and, individuals' knowledge sharing willingness is one of the strong predictors of actual individual knowledge sharing behaviour (Ajzen, 1991(Ajzen, , 2002.…”
Section: Tacit Knowledge Sharing and Audit Quality Inputsmentioning
confidence: 99%
“…The global financial crises have demonstrated the significant importance of high-quality financial reporting. Producing quality financial reporting is tied to each participant’s integrity in the financial reporting supply chain (Cameran et al , 2020; Sun et al , 2020). As one of those participants, auditors play a crucial role in achieving the quality of financial reporting worldwide by performing a high-quality audit of clients’ financial reports (Kueppers and Sullivan, 2010).…”
Section: Background On Audit Qualitymentioning
confidence: 99%
See 1 more Smart Citation